PERBEDAAN KELELAHAN PADA PERAWAT SHIFT MALAM RUANG RAWAT INAP ICCU DAN KANA DI RUMAH SAKIT X KUDUS - Yanuar Aji, Ikha Bayu; Widjasena, Baju; Jayanti, Siswi (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2011)
ABSTRACT Nurse is one of a person who gives health services which have a whole time besides patient that is 24 hours divided into 3 shift (morning, afternoon, and night). Work shift arrangement and time to rest giving in order to reduce level of exhaustion for nurses. Nevertheless, the impact from the arrangement of work shift still gives an effect to them. Kana and ICCU inpatient rooms are places of patient treatment which happened certain cases that is post-operation cases or accident cases, patient which have a serious or severe disease, patient with critical or serious condition so that for nurses mostly do a certain action either treatment of injuries or supervision for patient that get into trauma or injury according to standard of nursing. Work load of night shift nurses at Kana and ICCU rooms was high because of night shift nurses working upon 10 hours. This research was conducted in hospital ?X? Kudus at Kana and ICCU inpatient rooms. The objective of this study was to know about have or haven?t differences of research method was used survey with cross sectional approach. The samples of this research were 50 nurses. Reaction Timer was used to measured fatigue based on speed of light reaction. The result was analyzed by using t-test for unpaired samples with confidence level 95% and was obtained the value p < 0.05. Thereby, can be concluded that there are difference of fatigue toward night shift nurses at Kana and ICCU inpatient rooms in hospital ?X? Kudus. Therefore, the effort to tackle or handle the exhaustion was doing with utilization of time to rest by nurses effectively. Kata Kunci : Kelelahan, perawat  Kesmasindo. Volume 4(2) Juli 2011, hlm. 175-183